(untitled) (African Journal of Biomedical Research, 2021)
The impact of COVID-19 has been felt across the whole world. Economies of many countries have suffered yet there is still no cure for the pandemic. In this paper, we present a novel approach of conducting a clinical trial that may be employed in COVID-19 clinical trials. This approach can help in identifying a treatment policy or policies which can result in quicker recovery.